Perceptions of aging and health behavior: determinants of a healthy diet in an older German population - Bock, Christina; Schneider, Sven; Thiel, Ansgar (The journal of nutrition, health & aging, 2010)
The objectives of this study were to assess the association between perceptions of aging and health behavior, and to identify determinants of a healthy diet.